Deep Water - Poulson, Christine (Lion Hudson Plc, 2016)
A cure for obesity, worth billions. A death in a clinical trial. When patent lawyer Daniel Marchmont agrees to act for Calliope Biotech, he doesn't know what he's getting into. The first lawyer on the case is dead, and a vital lab book is missing. Daniel and his wife Rachel are hoping biotechnology will also provide a cure for their daughter Chloe, who suffers from a devastating genetic disorder. Then the unimaginable happens, and they face a moral dilemma that threatens everything. Meanwhile young researcher Katie Flanagan suspects something is very wrong in the lab. But knowledge is dangerous when someone is playing a perilous game...
Before Christine Poulson turned to writing crime novels, she was an academic with a PhD in History of Art and had published widely on nineteenth century art and literature. Her Cassandra James mysteries are set in Cambridge, UK. She is the author of Deep Water, Cold, Cold Heart, and An Air That Kills. Her short stories, published in Ellery Queen Mystery Magazine, CWA anthologies, and elsewhere, have been short-listed for a Derringer, the Margery Allingham Prize, and the CWA Short Story Dagger.